Executive Committee Minutes 2011-02-03 - Academic Senate:::::::::
Agenda approved. Minutes of 11/4 & 12/2 approved. Chair Report. President Report. Resolution on Creating a Diversity Stakeholder's Exploratory Committee approved for Senate agenda. Revisions to the RTP policy approved for the Senate agenda. One faculty member for emeritus status approved for Senate consent calendar. From EPC: Request to revive the University Program Review subcommittee referred to Structure and Functions. By-Laws: Change to Article III, Section 2 – Representative Proxies approved for Senate agenda. Question regarding membership of Excellence in Teaching Award committee. Faculty Governance Reassigned time for '11 – '12 approved. CFA Report. Statewide Senator Report. FSAC Report. EPC Report. Provost Report. Senate agenda approved. Questions for the Provost.